Equine protozoal myeloencephalitis in an equine in Colombia: case report - Maldonado Vera, María Camila (2020)
Equine Protozoal Myeloencephalitis (EPM) is an infectious neurological disease with a high percentage of mortality that affects equines that share habitat with their definitive host; however, it has not been widely reported in endemic regions. In Colombia, a country with wide distribution of the host, a veterinarian is consulted for a clinical case of an equine with neurological and muscular symptoms compatible with EPM. Antibiotic and anticoccidial treatment was immediately initiated when this pathology is suspected, and a blood sample was sent to confirm the diagnosis in the laboratory. The sample was positive for the sarcocystin toxin produced by the protozoan S. neurona. The equine responded positively and fully recovered five months after treatment. This case report shows the importance of taking this pathology into account as a differential diagnosis to establish an effective treatment as soon as possible, generating a favourable prognosis and, therefore, a recovery for the patient.